As bucólicas de Públio Virgílio Maro: tradução e estudo à luz de aparato etimológico e de simbologia da flora - Souza, Erick France Meira de (2019)
The Eclogues of Publius Vergilius Maro (roman poet from the classical period) have aroused, over more than two millennia, renewed interest in reading and literary studies, either by representative images such as the locus amoenus, by the exquisite composition of the poems amidst the flora which they present, or by the literary theme of the bucolic (inherited term from Greek for ‘herding’), whose features Vergil brings back and reshapes from remarkable sources such as the hellenistic poet Theocritus. On the other hand, concerning theory and methodology, advancements in the comparative method under an indo-european perspective have been considerable in the last decades, and that fact makes one wonder about what readings of these renowned poems would be possible by updating of the mentioned method, in such a way that etymology as well as phraseology, onomasiology and even discussions about cultural elements in general take up most of the thesis. At the beginning, there is a discussion about the course of the concept of philology in order to fashion a clearer idea of the applicability under perspective of the comparative method without, however, application of the formal stages of the classical philology (stemmatica, collatio etc.). It is also discussed, still in the beginning, the criteria about the adopted translation process, its benefits and drawbacks and what shape does it have in practice. After presenting the original poems in latin followed by their respective proposed translation, each poem has its own commentary according to the aforementioned proposal. Finally, the last chapter completes, with entries, the main commentaries by means of an examination of the flora, especially, present in the poems and of how the more literarily pertinent this presence has seemed to us, not being purely ornamental. As such, we resorted to a selection of terms of the flora and others of cultural interest (libertas, honos, amoenus, labor etc.) followed by images of this flora for better illustration. The conclusion is that, despite there being some questioning about the effectiveness of any etymological study, the studies and translations presented here should enable, as a display and updated fashion of the adopted method, a concrete feasibility to understand the poems without losing perspective of their literary context, notwithstanding some discussed opinions.